Relationship Between Sleep Quality and Quality of Life in Post-Stroke Patients at the Mangkurawang Community Health Center - Anisa Duwi Putri; Thomas Ari Wibowo (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Stroke is one of the leading causes of long-term disability and affects various aspects of patients’ lives. Post-stroke patients often experience pain, physical limitations, and psychological changes that may lead to sleep quality disturbances. Post-stroke conditions also cause long-termimpacts on patients’ physical, psychological, and social well-being, such as limb weakness, balance disorders, and difficulty walking, which may ultimately affect quality of life. Sleep quality disturbances in post-stroke patients have the potential to worsen physical and psychological conditions, resulting in an overall decline in quality of life. To determine the relationship between sleep quality and quality of life in post-stroke patients. Method: This study employed a quantitative research design with a cross-sectional approach. The sample consisted of 45 post-stroke patients selected using a total sampling technique. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while quality of life was assessed using the Stroke-Specific Quality of Life (SSQOL) questionnaire. Data were analyzed bivariately using the Spearman Rank correlation test. Result: The results showed that most respondents had poor sleep quality, with 33 respondents (71.1%), and poor quality of life, with 30 respondents (66.7%). The Spearman Rank correlation test revealed a p-value of 0.001 (< 0.05) and a correlation coefficient of 0.908. Conclusion: There is a significant relationship between sleep quality and quality of life in post- stroke patients.